Volleyball score sheet: Review and bibliometric analysis - Wahyuti, Sri Ayu; Siswantoyo,; Suhadi,; Nurfadhila, Risti; Nanda, Fitri Agung (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
Point scoring is often used as a useful skill performance indicator for athletes and coaches in volleyball matches. There is still limited research on the recording of “score sheet” match reports. This study aims to conduct an extensive bibliometric literature review on the “volleyball score sheet”. This research is qualitative research using a literature review method with a bibliometric analysis. Articles were searched using Publish or Perish (PoP) software with the Google Scholar database as the data source. There were 21 out of 673 articles found from the Google Scholar database from 1966 to 2021 analyzed in this study. Those selected were then managed using reference manager software, namely Mendeley version 1.19.8. After the database had been managed, this research classified and visualized it using VOSviewer software. Based on the literature review analysis conducted, it was found that 5 articles were suitable for analysis from 673 articles obtained from the search results. These data allow this paper to answer the question of what research trends in score sheet volleyball have been in the last 10 years. Some words that are not used can be linked and investigated in future research. Therefore, more topics can be developed based on these keywords such as affiliation, city and country. The elements mentioned above can provide a more comprehensive analysis. Overall, this review provided an appropriate reference point for further research on 'the volleyball score sheet'. Based on the analysis of the literature review conducted, it was found that the development of a comprehensive volleyball score sheet is needed, to facilitate scoring and avoid errors or loss of scoring as occurs in manual recording using a score sheet.